CONCEPTIONS OF MOTHERHOOD IN PROVERBS USED BY GHANAIAN WOMEN - Yitah, Helen (Proverbium - Yearbook, 2011)
Motherhood has been established as a key distinguishing factor of African gender relations. What remain unexplored are the circumstances under which African women find motherhood to be most fulfilling. In this paper I examine this subject by analyzing proverbs used by Kasena women from northern Ghana. The women take advantage of a socially sanctioned medium, the joking relationship that exists between a woman and her husband’s kin, to critique traditional constructions of motherhood via an innovative use of proverbs. From using clever and witty modifications of traditional proverbs, to creating brave new ones, Kasena women subvert, critique, and deconstruct the meaning of existing proverbs during joking in order to register their views on motherhood. Via their proverbs women indicate that motherhood is neither the only indicator of female identity nor the sole source of female fulfillment, as ‘traditional’ Kasem proverbs seem to suggest. They draw attention to other aspects of their identity, presenting themselves as persons with aspirations and ambitions for individual fulfillment and group well being.